Legal Determination of Brain Death — Polish Perspective - Jakub Mąkosa; Mariusz Wysokiński; Wiesław Fidecki; Kamil Kuszplak (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
The beginning of 2017 brought major changes in the legal norms concerning the declaration of permanent irreversible cessation of brain activity (brain death) and irreversible cardiac arrest before organ donation. The article presents changes that have occurred in this area and compares them with the previous regulations. As part of this study, a legal interpretation was also presented along with instructions on how to correctly apply the new regulations. (JNNN 2018;7(1):46–49)